Synthesis of metal nanoparticles for use as nanocatalysts in pet recycling - Rezende, Luciana Cristina Soto Herek; Oliveira, Jean Halison de; Zart, Vanessa Paola Miranda; Moisés, Murilo Pereira; Otto, Guilherme Piovezan; Fávaro, Sílvia Luciana (Acta Scientiarum. Technology, 2019)
This study investigated the efficiency of nickel nanocatalysts in the degree of PET conversion, under different conditions. The nanocatalysts were synthesized by the Pechini method at 500, 700 and 900ÂºC. PET depolymerization, via chemical glycolysis, was tested with varying time (3, 4 and 5 hours) and amount of catalyst (10, 35 and 60 mg). In order to evaluate the efficiency of these catalysts in PET depolymerization reactions, we followed a 23 factorial design with central point and applied a statistical analysis of variance (ANOVA). To optimize the degree of PET conversion, it was suggested to use 10 mg catalyst with 5h reaction time. Nickel nanocatalysts presented satisfactory results due to the possibility of using small amounts of catalyst, synthesized at low temperature, thus achieving a degree of conversion greater than 90%.